If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12X + 10 = -3X + 5 Reorder the terms: 10 + 12X = -3X + 5 Reorder the terms: 10 + 12X = 5 + -3X Solving 10 + 12X = 5 + -3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3X' to each side of the equation. 10 + 12X + 3X = 5 + -3X + 3X Combine like terms: 12X + 3X = 15X 10 + 15X = 5 + -3X + 3X Combine like terms: -3X + 3X = 0 10 + 15X = 5 + 0 10 + 15X = 5 Add '-10' to each side of the equation. 10 + -10 + 15X = 5 + -10 Combine like terms: 10 + -10 = 0 0 + 15X = 5 + -10 15X = 5 + -10 Combine like terms: 5 + -10 = -5 15X = -5 Divide each side by '15'. X = -0.3333333333 Simplifying X = -0.3333333333
| 7x+9=9-17x | | 10/n=40/12 | | 5x+35=10x | | x^3+8x^2+16x+1024=0 | | x^2-14=-24 | | 5x+45=11x+15 | | 2x^3+3x=6x^2+9 | | 2x^2+3x=6x^2+9 | | 6x^2+84=54x | | S//5=9 | | 8x+6=2(x-9) | | 3x=67y | | 12x+14=11x-13 | | 100-(34-(4-2)X3)/4 | | 4/9(-3/7)= | | 2x-7=8x-19 | | F(2)=2x+8 | | Inx+1=2 | | 3/8=4/12 | | 7x+9=4x+21 | | 100-(34-(4-2)X3/4 | | 6x^2-60x-y+161=0 | | 14=x/2=2 | | 12.5=0.5x | | 14=n/2=2 | | -8w=3/4 | | 56+24x+3x^2=8 | | 6t=t-7 | | 3x-7y-z=7 | | 8x/3-6=x/6-7/2 | | X+21+2x-6=180 | | 48+24x+3x^2=8 |